English for specific purposes curriculum evaluation from the social semiotic perspective - Sari, Latifa Ika; Rukmini, Dwi; Faridi, Abdurrachman; Mujiyanto, Januarius (Institute of Advanced Engineering and Science, 2024)
This paper presents an evaluation of an English for specific purposes (ESP) curriculum using the social semiotic perspective. This perspective highlights the importance of authenticity, multimodality, and communicative competence in ESP teaching and learning. Five main components of the ESP curriculum at the Port and Shipping Management Department of a Maritime Polytechnic in Indonesia were evaluated, including the syllabus, lesson plans, resources, teaching activities, and assessment. In conducting the evaluation, the authors developed an evaluation framework based on three existing frameworks, namely Stufflebeam’s context input process product (CIPP) model for evaluation, Kaewpet’s ESP program evaluation, and Tsou and Chen’s ESP program evaluation. Multiple data collection methods were used and multiple perspectives of research participants were invited. The findings of the study revealed that there were several problems in the ESP curriculum of the Port and Shipping Management Department. The main problem was the poorly designed syllabus that has caused drawbacks on the other components, such as irrelevant and unauthentic teaching materials and activities, low variety of teaching media, lack of multimodal resources used in the classroom, and low validity and reliability of assessments. Pedagogical implications regarding the results of the evaluation are also discussed.